Revolutionizing biogas generation: Polyethylene tubular digesters for household pig farms - Souvannasouk, Vannasinh; Oudtakhone Singthong; Phoukhanh Sayavongsa; Saneth Meas; Thanousinh Phaxaisithidet; Salongxay Fongsamouth (Maejo International Journal of Energy and Environmental Communication, 2023)
Manure decomposition from animal waste, including farm sludge, is a significant source of methane (CH4) and carbon dioxide (CO2) emissions, aggravating global warming. Addressing this issue is vital for the environment and pivotal in achieving sustainable development goals by combating pollution from agricultural activities. One promising solution is biogas production, which offers threefold benefits including mitigation of global warming, assurance of energy security, and efficient waste management. This can be achieved by optimizing the process using substrates that yield high biogas output while ensuring low water usage and retention. This study focuses on pig farms’ biogas potential of liquid and solid manure fractions performed with laboratory-scale batch digesters and enhanced polyethylene tubular digesters for evaluation. From the screening system, the biogas output from pig slurry resulted in CH4 and CO2 in 45 days, achieving 61.44 and 36.35%, respectively. After the initial screening experiment, polyethylene tubular digesters were implemented for biogas production at household pig farms and produced through fermentation in polyethylene tubular digesters under anaerobic conditions and are mainly composed of CH4 (60–64%) and CO2 (29–38%). This study suggested that the pig slurry could be a reliable biomass energy source for biogas and applicable to householders.